Pengaruh Model Project Based Learning Berbasis STEM Terhadap Keterampilan Berpikir Kreatif dan Motivasi Belajar Peserta Didik Pada Mata Pelajaran Biologi di SMAN 4 Palu - Palangi, Julmita; Jamhari, Mohammad; Agni, Raya; Laenggeng, Abd Hakim; Fardha, Rizka; Febriawan, Aan (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the effect of the STEM-based project-based learning (PjBL) model on students’ creative thinking skills and learning motivation in biology at SMA Negeri 4 Palu. The study used a quantitative approach with a quasi-experimental design, the population in this study were all grade X students of SMA Negeri 4 Palu in the 2024/2025 academic year consisting of 12 study groups with a total of 400 students. The sample was determined through purposive sampling, consisting of an experimental class (n=33) receiving PjBL-STEM learning and a control class (n=33) with conventional learning. Data were collected through creative thinking skills tests and learning motivation observation sheets, then analyzed using normality tests, homogeneity tests, and independent samples t-tests. The results showed that the PjBL-STEM model had a significant effect on improving creative thinking skills (Sig. = 0.023 <0.05) and learning motivation (Sig. = 0.000 <0.05). This finding confirms that the integration of the STEM approach in PjBL not only strengthens the cognitive but also the affective aspects, so that it can be used as a strategic alternative in developing a biology curriculum to foster 21st-century competencies.